(untitled) - Charles Rosen (New York, 1985)
The book offers striking insights into the work of artist-rebels, such as Ingres, constable, anf Géricault and suggests the ways in which the Romantics, and later the avant-garde Realist, broadened the definitions of art
Keywords: arts, modern - 19th century,realism in art,romanticism in art